1988
DOI: 10.1085/jgp.91.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Cross-bridge kinetics, cooperativity, and negatively strained cross-bridges in vertebrate smooth muscle. A laser-flash photolysis study.

Abstract: A B STR ACT The effects of laser-flash photolytic release of ATP from caged ATP [P3-1(2-nitrophenyl)ethyladenosine-5'-triphosphate] on stiffness and tension transients were studied in permeabilized guinea pig portal vein smooth muscle. During rigor, induced by removing ATP from the relaxed or contracting muscles, stiffness was greater than in relaxed muscle, and electron microscopy showed cross-bridges attached to actin filaments at an -45 ~ angle. In the absence of Ca 2+, liberation of ATP (0.1-1 mM) into mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
106
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(126 citation statements)
references
References 60 publications
19
106
1
Order By: Relevance
“…Caldesmon has been proposed to play a role in maintaining the high level of force during the latch state (31); however, it has not been fully determined as to whether or not this is one of its physiological roles with regards to contraction. Another area to be investigated with regards to a possible role for caldesmon is the theory of cooperativity, which suggests that cooperative activation of nonphosphorylated cross bridges occurs via phosphorylated cross bridges (36,39,39). It has been proposed that caldesmon may regulate the cooperative activation of cross bridges, but there has been little evidence supporting this potential role for caldesmon in vivo.…”
mentioning
confidence: 99%
“…Caldesmon has been proposed to play a role in maintaining the high level of force during the latch state (31); however, it has not been fully determined as to whether or not this is one of its physiological roles with regards to contraction. Another area to be investigated with regards to a possible role for caldesmon is the theory of cooperativity, which suggests that cooperative activation of nonphosphorylated cross bridges occurs via phosphorylated cross bridges (36,39,39). It has been proposed that caldesmon may regulate the cooperative activation of cross bridges, but there has been little evidence supporting this potential role for caldesmon in vivo.…”
mentioning
confidence: 99%
“…Tissue Preparation and Force Measurements-Mouse or rabbit portal veins were dissected, denuded of endothelium, cut into small strips (150 -250 m wide, 2-3 mm long), and mounted on a bubble plate or on a wire myograph system for force measurements (20) or in a muscle trough for photolysis experiments (21). The magnitude of contraction with 154 mM K ϩ was measured prior to stimulation with different agonists (20).…”
Section: Methodsmentioning
confidence: 99%
“…Apparatus and Photolysis Techniques-The UV laser for laser flash photolysis, a computer-controlled muscle trough system for solution exchange, the force transducer, and the data collection system have been described in detail previously (21,22). Protocols for Ca 2ϩ measurements, loading of the AM ester of Fluo3 into intact portal vein, pretreatment with cyclopiazonic acid, and introduction of caged compounds and their photolysis are described in the supplemental Experimental Procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Positive strain on the cross-bridges may also contribute to the slowing of the cycle. We have suggested that, given the high ratio of actin to myosin filaments in smooth muscle (Ashton et al 1975), it is possible that following the initial attachment of cross-bridges, at least some of the ATPase breakdown occurs through the slower associated state hydrolysis pathway (White et al 1997) and/ or cooperative cycling of non-phosphorylated myosin (Himpens et al 1988;Somlyo et al 1988;Vyas et al 1992;Butler & Siegman 1998).…”
Section: Phosphate Release Kinetics and Forcementioning
confidence: 99%
“…This high force-low phosphorylation state (catch-like state, also known as latch) occurs in smooth muscle after a decline in Ca 2þ concentration that initiates dephosphorylation of RLC (Dillion et al 1981). The high affinity of smooth muscle myosin for ADP (Vyas et al 1992;Fuglsang et al 1993;Nishiye et al 1993;Butler & Siegman 1998;Cremo & Geeves 1998;Gollub et al 1999), cycling of dephosphorylated cross-bridges (Vyas et al 1992;Butler & Siegman 1998;Somlyo et al 1988) and the effects of strain and RLC thiophosphorylation on product release (Khromov et al 2004) contribute to this catch-like state and will be one focus of this review along with a survey of some of the structure-linked changes evident in smooth muscle myosin.…”
Section: Introductionmentioning
confidence: 99%